2022
DOI: 10.1177/00469580221096528
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection by SARS CoV2 in Valle Del Cauca, Colombia: A Descriptive Retrospective Study

Abstract: Introduction: In coronavirus cases, reinfection has been associated with short-term immunity and genetic changes in viruses which allow them to escape from immune response, viral genotyping is required to make the precise diagnosis of reinfection, but the suspicion occurs in patients with more than 90 days between the tests and total improvement between them. We made a descriptive retrospective study with the cases of reinfection in Valle del Cauca, Colombia. Results: We found up to June 30, 3249 cases with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…It was found that during the pandemic phase, resistance to the drugs under study decreased (Klebsiella pneumoniae, producer of extended-spectrum beta-lactamase [ESBL], 32% pre-pandemic to 24% post-pandemic; K. pneumoniae, resistant to carbapenems, from 4% to a differential of 2%; Pseudomonas aeruginosa, resistant to carbapenems, from 12% to 8%; Acinetobacter baumann, resistant to carbapenems, from 12% to 8%); Pneumoniae, resistant to carbapenems, from 4% to a differential of 2%; Pseudomonas aeruginosa, resistant to carbapenems, from 12% to 8%; Acinetobacter baumannii, resistant to carbapenems, 23% to 9%), while Enteroccus faecium increased its resistance to vancomycin from (42% to 57%). When S. aureus was analyzed, there were no changes in the methicillin resistance rate, [24]. Studies carried out in Peru have shown high rates of resistance to ampicillin, cephalothin and nitrofurantoin at a rate of 72.6%, 82.3% and 88.7%, respectively.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was found that during the pandemic phase, resistance to the drugs under study decreased (Klebsiella pneumoniae, producer of extended-spectrum beta-lactamase [ESBL], 32% pre-pandemic to 24% post-pandemic; K. pneumoniae, resistant to carbapenems, from 4% to a differential of 2%; Pseudomonas aeruginosa, resistant to carbapenems, from 12% to 8%; Acinetobacter baumann, resistant to carbapenems, from 12% to 8%); Pneumoniae, resistant to carbapenems, from 4% to a differential of 2%; Pseudomonas aeruginosa, resistant to carbapenems, from 12% to 8%; Acinetobacter baumannii, resistant to carbapenems, 23% to 9%), while Enteroccus faecium increased its resistance to vancomycin from (42% to 57%). When S. aureus was analyzed, there were no changes in the methicillin resistance rate, [24]. Studies carried out in Peru have shown high rates of resistance to ampicillin, cephalothin and nitrofurantoin at a rate of 72.6%, 82.3% and 88.7%, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Antimicrobial resistance profiles have in some cases converged with regard to betalactams, with high sensitivities to cephalosporins and second and third generation quinolones. According to [24], in Colombia, uroculture studies were carried out before and during the COVID-19 pandemic, using different types of drugs such as ceftriaxone, cefepime, piperacillin/tazobactam, meropenem, ciprofloxacin and vancomycin [25]. It was found that during the pandemic phase, resistance to the drugs under study decreased (Klebsiella pneumoniae, producer of extended-spectrum beta-lactamase [ESBL], 32% pre-pandemic to 24% post-pandemic; K. pneumoniae, resistant to carbapenems, from 4% to a differential of 2%; Pseudomonas aeruginosa, resistant to carbapenems, from 12% to 8%; Acinetobacter baumann, resistant to carbapenems, from 12% to 8%); Pneumoniae, resistant to carbapenems, from 4% to a differential of 2%; Pseudomonas aeruginosa, resistant to carbapenems, from 12% to 8%; Acinetobacter baumannii, resistant to carbapenems, 23% to 9%), while Enteroccus faecium increased its resistance to vancomycin from (42% to 57%).…”
Section: Discussionmentioning
confidence: 99%
“…The use of antibiotics in these cases aims to treat concurrent bacterial infections or prevent their occurrence in patients with compromised immune systems, particularly those who are in a severe condition [ 83 ]. In their study on antibiotic resistance during COVID-19 in Valle del Cauca, Colombia, Hurtado et al [ 4 ] analyzed data from 31 hospitals and compared antibiotic resistance and consumption before (March 2018 to July 2019) and during (March 2020 to July 2021) the pandemic. The results showed an increase in the total number of bacterial isolates during the pandemic, accompanied by a significant decrease in resistance for four bug–drug combinations.…”
Section: Therapeutic Against Covid-19 In Colombiamentioning
confidence: 99%
“…This new coronavirus, known as severe acute respiratory syndrome coronavirus (SARS-CoV) 2 (SARS-CoV-2), is a virus containing a genome with 29,903 nucleotides and 29 proteins, belonging to the family Coronaviridae, subfamily Coronavirinae, and is the main cause of severe acute respiratory syndrome, also known as COVID-19 [ 1 , 2 , 3 ]. By the end of 2021 and early 2022, COVID-19 had infected 224 million people, and 4.6 million had died globally [ 4 ].…”
Section: Introductionmentioning
confidence: 99%